Using the ToBI transcription to record the intonation of Slovene - Volk, Jana (Linguistica (Ljubljana), 2012)
The paper presents ToBI, a transcription method for prosodic annotation. ToBI is an acronym for Tones and Breaks Indices which first denoted an intonation system developed in the 1990s for annotating intonation and prosody in the database of spoken Mainstream American English. The MAE_ToBI transcription originally consists of six parts - the audio recording of the utterance, the fundamental frequency contour and four parallel tiers for the transcription of tone sequence, ortographic transcription, indication of break indices between words and for additional observations. The core of the transcription, i. e. of the phonological analyses of the intonation pattern, is represented by the tone tier where tonal variation is transcribed by using labels for high tone and low tone where a tone can appear as a pitch accent, phrase accentand boundary tone. Due to its simplicity and flexibility, the system soon began to be used for the prosodic annotation of other variants of English and many other languages, as well as in different non-linguistic fields, leading to the creation of many new ToBI systems adapted to individual languages and dialects. The author is the first to use this method for Slovene, more precisely, for the intonational transcription and analysis of the corpus of spontaneous speech of Slovene Istria, in order to investigate if the ToBi system is useful for the annotation of Slovene and its regional variants.
Keywords: Corpus linguistics; discours spontané; intonacija; intonation; korpusno jezikoslovje; linguistique de corpus; méthode de transcription ToBI; Slovene; Slovenian Istria; slovenska Istra; slovenščina; spontani govor; ToBI; Tones and Breaks Indices; transkripcijska metoda ToBI